Quality of life, emotion dysregulation, attention deficit and psychiatric comorbidity in children and adolescents with vitiligo. (19th May 2020) - Ucuz, I.; Altunisik, N.; Sener, S.; Turkmen, D.; Kavuran, N.A.; Marsak, M.; Colak, C.
Summary: Background: Vitiligo is an acquired pigmentation disorder, which can have a negative effect on patient quality of life (QoL). Aim: To evaluate QoL and psychiatric comorbidity in paediatric patients with vitiligo. Methods: In total, 30 patients aged 8–18 years who were diagnosed with vitiligo and 30 age‐ and sex‐matched healthy controls (HCs) were included in the study. The Children's Depression Inventory, Screen for Child Anxiety Related Disorders, State‐Trait Anxiety Inventory for Children and Child Somatization Inventory were completed for both patients and controls. The Schedule for Affective Disorders and Schizophrenia for School Age Children‐Present and Lifetime Version (K‐SADS‐PL) was administered to all patients by a child psychiatrist. Families were also asked to complete the Pediatric Quality of Life Inventory and Emotion Regulation Checklist for children. Results: The K‐SADS‐PL evaluation showed that 90% of the patients in the vitiligo group had at least one psychiatric diagnosis, whereas this rate was 20% in the HCs ( P < 0.001). There were statistically significant differences between vitiligo and HCs in terms of anxiety, state and trait anxiety scores ( P < 0.05). Attention deficit and hyperactivity disorder (ADHD) was detected in 36.6% of the patients. Conclusion: The most important finding of this study is that anxiety disorders are more prominent than depression in childhood vitiligo. Another important finding of this study is that the prevalence of ADHD is significantly higher than the normal population.